Premature atherosclerosis and acute coronary syndrome in a child with end-stage renal disease - Tülay Becerir; Münevver Yılmaz; İlknur Girişgen; Neslihan Yılmaz; Dolunay Gürses; Furkan Ufuk; Gökay Nar; Selçuk Yüksel (SpringerOpen, 2021)
Abstract Background Although acute coronary syndrome is rare in children, it is the most important cause of mortality in children with end-stage renal disease. Case presentation Here, a 16-year-old pediatric patient, who has been on dialysis since the age of 3, and who was diagnosed with acute coronary syndrome and placed an emergency percutaneous transcatheter stent in the left anterior descending branch of the left coronary artery is presented. It is important that the present patient does not have any electrocardiography findings in favor of cardiovascular disease and that he cannot fully explain the complaint of chest pain due to his mental retardation. Conclusions Early detection of acute coronary syndrome is life-saving, especially in children with chronic kidney disease.